Tendencias y Retos de la educación Matemática en Costa Rica (ING) - Ruiz, Ángel; Chavarria, Jesennia; Mora, Federico (Uniciencia, 2003)
We describe and interpret the main trends and challenges in Mathematics Education in Costa Rica. This analysis allows us to understand the global perspective, going beyond a simple description to propose a set of actions to stimulate the progress Mathematics Education in Costa Rica and to contribute to the development of the country